Who are the adolescents saying "No" to cannabis offers. (1st June 2016) - Burdzovic Andreas, Jasmina; Pape, Hilde; Bretteville-Jensen, Anne Line
Highlights: Little is known about adolescents who remain non-users after being offered cannabis. This group differed from users and non-users who were never offered cannabis. Closer ties with parents and negative drug beliefs separated this group from users. Abstract: Background and aims: Adolescents who refuse direct cannabis offers and remain non-users represent a potentially very informative, yet surprisingly understudied group. We examined a range of risk and protective factors putatively associated with this poorly understood "cannabis-resilient" profile. Methods: Paper-and-pencil questionnaires assessing substance use, peer and family relations, and behavioral and personality characteristics were completed by 19, 303 middle- and high-school students from 82 schools in Norway (response rate 84%) Results: The lifetime prevalence of cannabis use was 7.6%. Another 10.4% reported no use of the drug despite having received recent cannabis offers. Results from the multinomial logistic regression revealed a set of characteristics differentiating adolescents who resisted such offers from those who: (a) neither received the offers nor used, and, more importantly, (b) used the drug. Specifically, parent-child relationship quality, negative drug-related beliefs, absence of close relationships with cannabis-users, low delinquency, no regular tobacco use, and infrequent alcohol intoxication were all associated with increased odds of being in the cannabis-resilient vs. cannabis-user group. This pattern of results was comparable across middle- and high-school cohorts, but the parent-child relationship quality and delinquency were significantly associated with cannabis-resilient vs. cannabis-use outcome only among younger and older adolescents, respectively. Conclusions: Among other low-risk characteristics, better relationships with parents and beliefs that drug use is problematic were associated with adolescents' refusals to accept cannabis offers. These results may have implications for novel preventive strategies targeting cannabis-exposed adolescents.